2019
DOI: 10.3390/app9112259
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Electrode Modification to Upgrade the Bioelectrocatalytic Oxidation of Tannery Wastewater Using Acclimated Activated Sludge

Abstract: Effective and eco-friendly technologies are required for the treatment of tannery wastewater as its biological toxicity and large volume leads toground water pollution. Hydrophobic (unmodified carbon felt) and hydrophilic modified carbon felt with Linde Type A zeolite (LTA zeolite) and bentonite were examined for their effects on bacterial attachment, current generation, and tannery wastewater treatment efficiency. Chronoamperometry and cyclic voltammetry confirmed the higher electron transfer obtained with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Tenacious, resistant, and exoelectrogenic microorganisms used in bioelectrochemical systems (BES) can perform the dual function of degrading pollutants and recovering in the form of electrical energy, the energy resulting from the oxidation of these pollutants. Indeed, previous studies reported that exoelectrogenic populations have favorably demonstrated an added value for the treatment of recalcitrant pollutants, such as azo dyes, petroleum hydrocarbon, and heavy metals (Adelaja et al, 2015 ; Choudhury et al, 2017 ; Monzon et al, 2017 ; Grattieri and Minteer, 2018 ; Vijay et al, 2018 ; Askri et al, 2019 ; Elabed et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Tenacious, resistant, and exoelectrogenic microorganisms used in bioelectrochemical systems (BES) can perform the dual function of degrading pollutants and recovering in the form of electrical energy, the energy resulting from the oxidation of these pollutants. Indeed, previous studies reported that exoelectrogenic populations have favorably demonstrated an added value for the treatment of recalcitrant pollutants, such as azo dyes, petroleum hydrocarbon, and heavy metals (Adelaja et al, 2015 ; Choudhury et al, 2017 ; Monzon et al, 2017 ; Grattieri and Minteer, 2018 ; Vijay et al, 2018 ; Askri et al, 2019 ; Elabed et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites are effective for purifying water and gases [51][52][53]. There are numerous works on their production using coal ash [54][55][56][57][58].…”
Section: Adsorption By Zeolites Synthesized From Rice Husksmentioning
confidence: 99%
“…Tough, resilient, and exoelectrogenic microorganisms from extreme environments (Cherif et al, 2017;Ben Abdallah et al, 2018;Askri et al, 2019) used as inoculums in microbial electrochemical systems could fulfill the double function of degrading the TBZ and recovering the energy resulting from its oxidation, or at least directly follow its fate in solution by measuring the specific current of its oxidation. Previous studies have demonstrated that exoelectrogenic populations have favorably contributed to the treatment of recalcitrant pollutants, such as azo dyes, heavy metals, and petroleum hydrocarbons (Grattieri and Minteer, 2018;Vijay et al, 2018;Elabed et al, 2019;Askri et al, 2020). Askri et al (2020) demonstrated the high performance of microbial bioanodes enriched from bacterial communities of Tunisian extreme environment saline sediments and real textile wastewater for degrading dyes at 91 ± 3% and recovering electric current streams up to 12.5 ± 0.2 A/m 2 .…”
Section: Introductionmentioning
confidence: 97%